Quantifying the internal deformation of the rodent spinal cord during acute spinal cord injury – the validation of a method. Issue 4 (11th March 2016) - Bhatnagar, Tim; Liu, Jie; Yung, Andrew; Cripton, Peter; Kozlowski, Piotr; Tetzlaff, Wolfram; Oxland, Thomas
Abstract : Visualization and analysis of the rodent spinal cord subject to experimental spinal cord injury (SCI) has almost completely been limited to naked-eye observations, and a single measure of gross spinal cord motion due to injury. This study introduces a novel method which utilizes MRI to quantify the deformation of the rodent spinal cord due to imposed, clinically-relevant injuries – specifically, cervical contusion and dislocation mechanisms. The image registration methods were developed using the Advanced Normalization Tools package, which incorporate rigid, affine and deformable registration steps. The proposed method is validated against a fiducial-based, 'gold-standard' measure of spinal cord tissue motion. The validation analysis yielded accuracy (and precision) values of 62 μm (49 μm), 73 μm (79 μm) and 112 μm (110 μm), for the medio-lateral, dorso-ventral and cranio-caudal directions, respectively. The internal morphological change of the spinal cord has never before been quantified, experimentally. This study demonstrates the capability of this method and its potential for future application to in vivo rodent models of SCI.